The Pegomya maculata species group (Diptera Anthomyiidae) in Europe, with description of a new species - Michelsen, Verner; Ackland, D. Michael (Zootaxa, 2009)
The number of species in the Pegomya maculata species group is raised from three to four with the description of a new, Holarctic species, P. grahami sp. nov. The other species, P. maculata Stein, P. atricauda Ringdahl and P. macrophthalma Griffiths, are redescribed. The number of species in Europe is raised from two to four. Two species, P. grahami (previously recorded as P. maculata) and P. macrophthalma, are also Nearctic. Pegomya maculata is the only species known from the female, but descriptions are given of 2–3 unidentified female morphospecies matching the species group. A lectotype is designated for Pegomyia maculata Stein, 1906.